2016
DOI: 10.1080/21622965.2015.1072535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and school type on unconstrained, phonemic, and semantic verbal fluency in children

Abstract: Biological and cultural factors have been found to have a significant influence on cognitive development and performance in neuropsychological instruments such as verbal fluency tasks (VFT). Variations of traditional VFT, involving unconstrained word production and increased retrieval times, may provide further data regarding the executive, attentional, mnemonic, and linguistic abilities involved in VFT. As such, the aim of this study was to investigate the impact of age and school type on the performance of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
5
1
5
Order By: Relevance
“…Moreover, anxiety and depression rates of SMA patients varied signi cantly between different types of schooling, with lower rates among patients enrolled in personalized schools compared with those attending traditional schools. Jacobsen et al found that school type has an important impact on cognitive stimulation, when private schools provide more personalized methods [43]. The reason for the signi cant differences in anxiety and depression in our study may be that personalized schools provide special support for SMA children, such as special desks and suitable classroom locations and recovery equipment.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, anxiety and depression rates of SMA patients varied signi cantly between different types of schooling, with lower rates among patients enrolled in personalized schools compared with those attending traditional schools. Jacobsen et al found that school type has an important impact on cognitive stimulation, when private schools provide more personalized methods [43]. The reason for the signi cant differences in anxiety and depression in our study may be that personalized schools provide special support for SMA children, such as special desks and suitable classroom locations and recovery equipment.…”
Section: Discussionmentioning
confidence: 69%
“…Sin embargo, a fin de poder constatar esta hipótesis sería necesario evaluar poblaciones de niños más pequeños, así como realizar estudios longitudinales que permitan observar el seguimiento de los cambios en el desarrollo. Además, sería necesario ampliar la muestra considerando participantes de diferentes estratos socio-económicos, ya que existen variables sociales que impactan diferencialmente en el desarrollo lingüístico Jacobsen, et al, 2017;Jacobsen, et al, 2016).…”
Section: Discussionunclassified
“…En general, se propone que en las tareas de fluencia o fluidez verbal participan los procesos de memoria de trabajo, atención sostenida, monitoreo e inhibición (componente ejecutivo), memoria semántica, estrategias de búsqueda y activación de ítems léxicos (Gaillard et al, 2000;García Coni & Vivas, 2014;Marino & Alderete, 2008;Marino & Alderete, 2010;Shao, et al, 2014). Diversas investigaciones han propuesto que tanto factores biológicos como socioculturales tienen incidencia en el desempeño en dichas tareas (Jacobsen et al, 2016;Kochhann et al, 2017;Van der Elst, Hurks, Wassenberg, Meijs, & Jolles, 2011).…”
Section: Introductionunclassified
See 2 more Smart Citations